Objective and Subjective Factors Influence on Demand of Drainage by Pumping in Red River Delta - Hanh, Dang Ngoc (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 3, 2010)
Abstract. The demand for newly constructing of drainage pumping station in Red river delta has increased recently. Total drainage volume for the whole region in 2006 was 2406.8m 3 /s, and it was predicted to increase to 5181.3m 3 /s in 2020 [1]. The average drainage coefficient for the year from 2010 to 2020 will be 7.0 l/s per hectar, three and a haft time higher than the average drainage coefficient for the period from 1954 to 1973; 1.8 times higher than 1973 to 1976 and 1.3 times higher than 1976 to 2000. This article aims to provide the primary analysis of objective (drainage requirement) and subjective factors (socio-economic condition, psychology, information, etc) influencing on the demand of drainage. The out come shows that the draingae demand seems to be impacted by subjective factors rather than objective ones.